2020
DOI: 10.1021/acs.macromol.0c02100
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chain Polarity on Ion and Polymer Dynamics: Molecular Volume-Based Analysis of the Dielectric Constant for Polymerized Norbornene-Based Ionic Liquids

Abstract: Norbornene-based polymerized ionic liquids (PILs) were systematically prepared to understand the role of PIL architecture and linker on the ionic conductivity (σ DC ), segmental dynamics, and dielectric constant. In PILs with two-or one-armed imidazolium (Im + )-bis(trifluoromethanesulfonyl)imide (Tf 2 N − ) pendants, their dynamics and polarity were tuned by incorporating either oxyethylene [(OCH 2 CH 2 ) x = (OE) x , x = 1 or 3] or alkylene [(CH 2 ) 2 ] moieties as linkers between the norbornene and imidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…These values give γ ≈ 0.08−0.9 if we assume that l B ≈ 10 nm (a dielectric constant of ϵ ≈ 5.6). We note also that a number of measurements 49,50 of PILs have indicated that very high static dielectric constants (ϵ ≈ 50−100) are possible, which would lower the value of γ further.…”
Section: ■ Resultsmentioning
confidence: 83%
“…These values give γ ≈ 0.08−0.9 if we assume that l B ≈ 10 nm (a dielectric constant of ϵ ≈ 5.6). We note also that a number of measurements 49,50 of PILs have indicated that very high static dielectric constants (ϵ ≈ 50−100) are possible, which would lower the value of γ further.…”
Section: ■ Resultsmentioning
confidence: 83%
“…This placement of the imidazolium moiety was further explored by Kuray et al, who found that materials with the charged moiety placed in a pendant had a greater σ than those with the functionalization directly in the polymer backbone . Choi et al explored the difference in σ between materials with an alkyl spacer versus PEO spacers and showed the PEO-containing PILs were significantly more conductive because of the relatively flexible and polar nature of the PEO spacer that behaves as a plasticizer and solvator. , Other PEO structures have also been explored, such as linear side chain versus cyclic side-chain, as well as utilizing PEO as the polymeric backbone with imidazolium pendant moieties . Ikeda et al explored the length of tail off of the imidazolium pendant and found it has no major influence on T g or conductivity .…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, the decoupling of ion dynamics from segmental motion is the most promising approach to achieve high ionic conductivity in polymer electrolytes at room temperature. Moreover, there have been a series of studies to examine the effect of tuning of cation/anion size, 30,31 position of ions (either in the main chain or in the side chain) of PIL, 19,29,32,33 variation of molecular weight, 18 changing the space between neighboring PIL chains, 13 pressure exerted during conductivity measurement, 1 variation of chain length, 34 glass transition temperature ( T g ), 14,30,35 chain polarity, 36 etc., on the change of ionic transport in PIL systems. Dielectric spectroscopic (DS) technique is reported to be the most popular method to investigate ionic conductivity, ion transport and relaxation mechanism in electrolyte systems 29,37–39 .…”
Section: Introductionmentioning
confidence: 99%